2006
DOI: 10.1587/elex.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Effective mobility and interface-state density of La2O3 nMISFETs after post deposition annealing

Abstract: Abstract:In this paper, we reported the effective mobility and the interface-state density of La 2 O 3 nMISFETs fabricated under different post deposition annealing (PDA) conditions; annealing temperature (300 • C -600 • C) and ambient (N 2 or O 2 ). High effective mobility of 312 cm 2 /Vs and low interface-state density of 6 × 10 10 cm −2 /eV were obtained from La 2 O 3 nMISFET with equivalent oxide thickness (EOT) of 1.7 nm after PDA at 300 • C in N 2 ambient for 10 minutes. Gate leakage current density was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Among high-k materials, RE-oxides are promising, since they can directly contact with Si substrate by forming silicate layer [3]. For instance, a satisfactory interfacial property with a peak effective mobility of over 300 cm 2 /Vs has been reported with La 2 O 3 dielectrics [4]. However, the excess oxygen supplied from the gate electrode to the La 2 O 3 dielectric increases the EOT especially with high-temperature processes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Among high-k materials, RE-oxides are promising, since they can directly contact with Si substrate by forming silicate layer [3]. For instance, a satisfactory interfacial property with a peak effective mobility of over 300 cm 2 /Vs has been reported with La 2 O 3 dielectrics [4]. However, the excess oxygen supplied from the gate electrode to the La 2 O 3 dielectric increases the EOT especially with high-temperature processes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that La 2 O 3 can achieve an EOT below 1 nm by forming a La-silicate layer with a k-value ranging from 8 to 14 at Si interface with fairly nice performance (2). However, it also suffers from the fixed charge-related mobility degradation at an EOT below 1.3 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other high-k materials, La 2 O 3 has been considered as a potential candidate for the long-term replacement of SiO 2 because of its relatively high dielectric constant and band offsets to silicon [1,2]. Moreover, since La 2 O 3 -gated transistors have presented good initial electrical characteristics [3], the research on this material should advance to the next stage where reliability data are collected and the understanding of the mechanisms for dielectric degradation and breakdown is identified in order to minimize the sources that lead to failure. In this report, we studied the impact of stress polarity on the breakdown and electrical degradation mechanisms of W-La 2 O 3 gated MOSFETs.…”
Section: Introductionmentioning
confidence: 99%